UZNANIE OJCOSTWA W TOKU PROCESU O USTALENIE OJCOSTWA PRZEZ MĘŻCZYZNĘ BĘDĄCEGO STRONĄ W TYM POSTĘPOWANIU - Stojanowska, Wanda; Wypierowska, Paulina (Zeszyty Prawnicze, 2016)
ADMISSION OF PATERNITY DURING A PATERNITY CASE BY THE MAN WHO IS A PARTY IN THE PROCEEDINGS Summary The subject of this article is the provision of the new § 2 added to Art. 72 of the Polish Family and Guardianship Code (Kodeks rodzinny i opiekuńczy) in the amendment of 6 November 2008, which came into force on 13 June 2009. Under this provision, “the admission of paternity is not possible if paternity proceedings have already started.” The provision has provoked heated argument in the juristic literature, boiling down to the question whether the admission of paternity by the man who is a party in a paternity case is admissible and possible. Most authors have considered this admissible and, moreover, they have strongly criticised the wording of the new provision, which is very unclear. In view of the controversy in the doctrine, it was highly necessary to examine data on paternity cases to establish the trend in court decisions, that is how the courts are interpreting the provision of § 2 of Art. 72 of the Family and Guardianship Code, whether they are accepting the interpretation of this provision as allowing the admission of paternity in court while a paternity case is already in progress, or whether they are treating the this provision as a prohibition on the admission of paternity in such circumstances and strictly observing it. The article contains an analysis of the research data from 50 paternity cases heard in three family courts in the district of Warsaw following the amendment. 84% of the cases concluded with the man who was the party in the case admitting paternity. Thus the court decisions show that such a solution is admissible, and the interpretation of the provision adopted by the majority of representatives of the doctrine is being implemented in forensic practice.